A SYSTEMATIC ANALYSIS OF THE NATURE AND PATTERNS OF SHADOW ECONOMY - Zaveruha M.M. (Pressing Problems of Public Administration, 2015)
The analysis of the formation and functioning of the shadow economy. The need for a systematic approach to the nature and characteristics of the shadow economy.